Combined effects of caloric restriction and branched-chain amino acid supplementation on body composition and exercise performance in elite wrestlers - Mourier, A.; Bigard, A. X.; de Kerviler, E.; Roger, B.; Legrand, H.; Guezennec, C. Y. (International Journal of Sports Medicine, 1997)
Twenty-five competitive wrestlers restricted their caloric intake (28 kcal.kg-1.day-1) for 19 days, using a hypocaloric control (hC, n = 6), hypocaloric high-protein (hHP, n = 7), hypocaloric high-branched-chain amino acid (hBCAA, n = 6), hypocaloric low-protein (hLP, n = 6) diet to determine the effects of caloric restriction on body composition and performances versus control diet (C, n = 6). Anthropometric parameters (weight, percent body fat) and adipose tissue (AT) distribution measured by magnetic resonance imaging (MRI) obtained before and after diet, were compared. A significant highest body weight loss (-4 kg, p < 0.05) and decrease in the percent of body fat (-17.3%, p < 0.05) were observed for subjects of the hBCAA group. Subjects of the hBCAA group exhibited a significant reduction (-34.4%, p < 0.05) in abdominal visceral adipose tissue (VAT). There was no change in aerobic (VO2max) (p > 0.75) and anaerobic capacities (Wingate test) (p > 0.81), and in muscular strength (p > 0.82). We conclude that under our experimental conditions, the combination of moderate energy restriction and BCAA supplementation induced significant and preferential losses of VAT, and allowed maintainance of a high level of performance.